2020
DOI: 10.3846/tede.2020.13863
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sustainable Finance in Achieving Sustainable Development Goals: Does It Work?

Abstract: The World Bank and International Monetary Fund reported that the achievement of the 17 Sustainable Development Goals (SDGs) requires an escalation of development finance. The report Scaling Finance for the Sustainable Development Goals highlighted the urgency of the efforts to realize SDGs in encouraging financial innovation to move quickly. Even if the role of finance in achieving SDGs is unquestionable, few scientific studies have addressed these issues. We tried to fill the existing research gap. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(59 citation statements)
references
References 43 publications
2
37
0
1
Order By: Relevance
“…On the other hand, in the current strategy aiming to achieve as many as 17 different goals, it was decided to immediately identify the goals and appropriate indicators that should be related to each other. Moreover, in this case, some of these assumed relationships are not observed in reality, which was confirmed, among others, by the results of the research presented in [4,5], examining in detail the relationship between the various goals of the strategy.…”
Section: Introductionsupporting
confidence: 70%
“…On the other hand, in the current strategy aiming to achieve as many as 17 different goals, it was decided to immediately identify the goals and appropriate indicators that should be related to each other. Moreover, in this case, some of these assumed relationships are not observed in reality, which was confirmed, among others, by the results of the research presented in [4,5], examining in detail the relationship between the various goals of the strategy.…”
Section: Introductionsupporting
confidence: 70%
“…In 2017, a framework for Sustainable Finance was introduced, presenting a Sustainable Finance typology based on the value created -ranking of financial value, social impact, and environmental impact factors as well as the horizon (Schoenmaker, 2017). Ziolo et al (2021) confirmed the relationship between achievement of SDGs and sustainable financing, which was the strongest in countries that use Sustainable Finance 3.0, oriented to social-environmental impact first and a common good value in the long run. The paper adapts this data by incorporating FinTech PEST environment assessment results and carrying out comparative data analysis to assess whether any link or trend 9 shows the results of the comparative analysis.…”
Section: Components Of the Environmentsupporting
confidence: 56%
“…Meanwhile for SDG achievement assessment, the data generally partially covering the years 2010-2020 were used. Therefore, SDG achievement data from 2016 were used (Ziolo et al, 2021). Some limitations were observed in the comparative analysis as well -Lithuania and Spain as representatives of the Conventional Finance model took average positions in the FinTech PEST environment ranking despite poor performance in the achievement of SDGs and the Sustainable Finance, therefore, stood out as the only countries that did not follow the general trend of the results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations